ANALISIS PREDIKSI KEBANGKRUTAN PADA BANK UMUM SYARIAH DEVISA DI INDONESIA DENGAN MENGGUNAKAN METODE ALTMAN Z SCORE TAHUN 2013 SAMPAI 2015 - Khusnudin, Imam; Munawir, Munawir (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2022)
The aim is to find out the Altman Z-Score variables are able to predict bankruptcy and to determine the significant effect between working capital/total assets, retained earnings/total assets, earnings before interest and taxes/total assets, and book value equity/total liabilities on predictions. Bankruptcy in the Foreign Exchange BUS in Indonesia for the period 2013-2015. The results of the first test show that during the period 2013-2015 Foreign Exchange BUS is predicted to be in a healthy condition, except in the second quarter Mega Syariah is predicted to go bankrupt. And the results of the second test show that partially working capital/total assets and retained earnings/total assets have no effect on the prediction of bank bankruptcy, while the variables of earnings before interest and taxes/total assets and book value of equity/total liabilities have a significant effect on bankruptcy prediction. From the results of the f test simultaneously the four Altman Z-Score variables together have a significant effect on the prediction of bank bankruptcy. And the results of the multiple correlation determinant that 36% of the Z-Score value is influenced by the variables of MKTA, LDTA, LSBPTA, and NBETK.